Region-independent active CNS net uptake of marketed H+/OC antiporter system substrates - Bällgren, Frida; Hu, Yang; Li, Shannuo; van de Beek, Lara; Hammarlund-Udenaes, Margareta; Loryan, Irena (Frontiers in Cellular Neuroscience, 2024)
The pyrilamine-sensitive proton-coupled organic cation (H+/OC) antiporter system facilitates the active net uptake of several marketed organic cationic drugs across the blood-brain barrier (BBB). This rare phenomenon has garnered interest in the H+/OC antiporter system as a potential target for CNS drug delivery. However, analysis of pharmacovigilance data has uncovered a significant association between substrates of the H+/OC antiporter and neurotoxicity, particularly drug-induced seizures (DIS) and mood- and cognitive-related adverse events (MCAEs). This preclinical study aimed to elucidate the CNS regional disposition of H+/OC antiporter substrates at therapeutically relevant plasma concentrations to uncover potential pharmacokinetic mechanisms underlying DIS and MCAEs. Here, we investigated the neuropharmacokinetics of pyrilamine, diphenhydramine, bupropion, tramadol, oxycodone, and memantine. Using the Combinatory Mapping Approach for Regions of Interest (CMA-ROI), we characterized the transport of unbound drugs across the BBB in specific CNS regions, as well as the blood-spinal cord barrier (BSCB) and the blood-cerebrospinal fluid barrier (BCSFB). Our findings demonstrated active net uptake across the BBB and BSCB, with unbound ROI-to-plasma concentration ratio, Kp,uu,ROI, values consistently exceeding unity in all assessed regions. Despite minor regional differences, no significant distinctions were found when comparing the whole brain to investigated regions of interest, indicating region-independent active transport. Furthermore, we observed intracellular accumulation via lysosomal trapping for all studied drugs. These results provide new insights into the CNS regional neuropharmacokinetics of these drugs, suggesting that while the brain uptake is region-independent, the active transport mechanism enables high extracellular and intracellular drug concentrations, potentially contributing to neurotoxicity. This finding emphasizes the necessity of thorough neuropharmacokinetic evaluation and neurotoxicity profiling in the development of drugs that utilize this transport pathway.